Does environmental attention differ during walking, jogging, and cycling in greenways? Evidence from eye movement responses to videos - Pan, Yidian; Liu, Chang; Liu, Yue; Liu, Yuhan; Zhao, Jiayi; Zheng, Yongrong; He, Songjun (Frontiers in Psychology, 2025)
IntroductionGreenways accommodate various path-based physical activities (PPAs). This study aimed to examine the similarities and disparities in environmental attention and cognitive responses during different greenway PPAs.MethodThe eye movements of 26 participants were recorded while watching a greenway video during walking, jogging, and cycling in counterbalanced sequences.ResultsThe results of the Kruskal–Wallis test indicate that (1) in terms of similarities, vegetation received the most attention with a higher number of fixations (rNF) and a greater total fixation duration (rTDF) compared to other areas of interest (AOIs). However, roads demanded more cognitive activities for spatial orientation as indicated by the longest average fixation duration (rAFD). (2) Regarding disparities, walkers showed a greater fascination with vegetation, displaying a higher rTDF than joggers and cyclists and a longer relative first fixation duration (rDFF) compared to other AOIs. Joggers demonstrated more concentrated attention with the lowest average blink rate (AB), producing a heatmap dominated by longer fixations, and they experienced a higher rAFD than walkers and cyclists on roads. Cyclists were more strongly attracted toward distant views, as evidenced by their flattened-shaped heatmap, and open water bodies drew their attention as their rNF on water exceeded that observed in other PPAs.DiscussionTherefore, clear and varied vegetation landscapes, distinct and noticeable roads, and open water surfaces offering distant views can better hold the attention of different PPA exercisers and minimize their mental fatigue. The research contributes to enhancing the role of greenways in promoting physical activity and fostering psychological wellbeing through activity-adapted environmental interactions.